Pengembangan Instrumen Tes Literasi Numerasi dengan Konteks Budaya Minangkabau untuk Melatih kemampuan Literasi Numerasi Siswa - Sari, Dian Rahma; Isnaniah, Isnaniah; Zakir, Supratman; Imamuddin, M (Juring (Journal for Research in Mathematics Learning), 2025)
This study began with the problem of lack of numeracy literacy test instruments with the cultural context and the low ability of student numeracy literacy in SMP Negeri 3 Bukittinggi. Based on the national education system, teachers should facilitate learning for students with local culture. The purpose of this study was to produce numeracy literacy test instruments with the Minangkabau cultural context to practice valid, practical and effective numeracy literacy apabilities. The method used is Research and Development (R&D) with the ADDIE model (analysis, design, development, implementation, evaluation). Researchers use student response questionnaires and teacher response questionnaires to determine the validity and practicality of the test. Furthermore, to find out the effectiveness of researchers' products using tests. Based on the results of the validity level research and test instruments obtained 79.4% with valid criteria. The practicality level obtained 84.04% with very practical criteria from student responses and 82% with very practical criteria from the teacher's response. Furthermore, the level of effectiveness obtained 95.83% with very effective criteria. Based on this it can be concluded that the numeracy literacy test instrument with the Minangkabau cultural context to practice the ability of numeracy literacy has met valid, practical and effective criteria.